Indirubin-incorporated biodegradable PHB microbeads and its application for functional facial cleanser - Choi, Yura; Choi, Kwon Young (Dyes and Pigments, 2025)
In this study, we report the production of biodegradable microbeads using the poly [(R)-3-hydroxybutyric acid] (PHB) polymer. To introduce functionality, we engineered Escherichia coli strains to produce biodegradable PHB by expressing indole oxidase, enabling the synthesis of biodegradable polymers containing either indigo or indirubin. The formation of indigo or indirubin or both is dictated by the symmetrical or asymmetrical dimerization of oxidized indole products, which depends on the specific oxidation position. To increase the content of indirubin—a compound with known anticancer properties—relative to indigo (commonly used as a dye for denim), isatin was supplied during synthesis. This approach yielded indirubin-PHB biodegradable films with enhanced indirubin content. Furthermore, during the film fabrication process, photodegradation of indigo was induced, further enriching the relative indirubin content ratio. Using these indirubin-PHB films, biodegradable microbeads with diameters below 200 μm was successfully produced. Characterization of these microbeads confirmed the incorporation of indirubin, resulting in functional biodegradable microbeads. Finally, a prototype facial cleanser containing indirubin-PHB microbeads was developed, suggesting the potential of these eco-friendly microbeads as cosmetic ingredients for future applications.
Keywords: 3-hydroxybutyric acid; Dimerizations; Engineered escherichia coli; Facial cleanser; Functionals; Indirubin; ITS applications; Microbeads; PHB; Polyhydroxybutyrate; Biodegradability; Facial cleanser; Indirubin; Microbeads; PHB; Polyhydroxybutyrate